Från engelsk-svensk namnordbok till svensk-engelsk - Törnqvist, Lars (Nordiske Studier i Leksikografi, 2001)
Engelsk-svensk namnordbok, published in 1996, is a bilingual dictionary comprising 3600 proper names which are spelled differently in English and Swedish. The articles contain short explanations, usually consisting of the genus proximum only. The aim of the author was to create a tool for translators, but many people are actually using the dictionary for other purposes, e.g. as a passive reception dictionary or as a language learning tool. The author is currently engaged in compiling a Swedish-English proper-name dictionary, which isn't justa reversed version of the English-Swedish counterpart, but a dictionary with a wider scope. As the English pronunciation of the names i.vill be given in the nei.v dictionary, it i.vill comprise not only names with different spelling, but also names i.vhich are pronounced differently in Swedish and English.